118k views
2 votes
4x + 2(x – 3) = 4x + 2x – 11Part A: Solve the equation and write the number of solutions. Show all the steps. Part B: Name one property you used to solve this equation.

User Hkurabko
by
5.0k points

1 Answer

2 votes

Part A:

The given equation is:


4x+2(x-3)=4x+2x-11

Combine like terms:


4x+2(x-3)=6x-11

Using the distributive property, expand the expression:


4x+2x-6=6x-11

Combine like terms:


6x-6=6x-11

Using the Substitution Property of Equality, it follows that:


\begin{gathered} 6x-6x-6=6x-6x-11 \\ -6=-11 \end{gathered}

Since the statement -6 = -11 is false, it follows that there is no solution to the equation

Therefore, the number of solutions is 0

Part B: One property used is the Subtraction Property of Equality

User LawMan
by
6.3k points